Multigrading and child achievement - Gian Paolo Barbetta; Giuseppe Sorrenti; Gilberto Turati (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2018)
We exploit Italian law DPR 81/2009, which determines class composition, as an instrument to identify the causal effect of grouping students of different grades into a single class (multigrading) on children cognitive achievement. This article focuses on 7-year-old students - those at the beginning of their formal education. Results suggest that attendance in multigrade classes versus single-grade classes increases students' performance on standardized tests by 15-20 percent of a standard deviation. The positive impact of multigrading only appears for children sharing their class with peers from higher grades and is relatively stronger for students from disadvantaged backgrounds.
Keywords: I26; I28; R53; 330; Multigrade classes; child development; peer effects; rural areas